Bonding characteristics at the Ni-alumina composite interface via STEM-based EELS technique. (18th July 2008) - Jing, Mao-xiang; Li, Dong-hong; Shen, Xiang-qian; Li, Wang-xing
Bonding characteristics of the metal and ceramic interfaces are significant to understand toughening mechanisms and design metal-ceramic composites. The Ni/alumina composite has been prepared by hot press-sintering of Ni-coated alumina powders and the bonding characteristics at the Ni-alumina composite interface have been studied by use of transmission electron microscopy (TEM)-based electron energy loss spectroscopy (EELS) techniques. From Al L2, 3, Ni L2, 3, and O K-edge EELS spectrum obtained, it can be reasoned that the interface in the Ni/alumina composite mainly consists of aluminum-terminated alumina and metallic Ni, and the bonding between them is primarily nonreactive with a nonionic ?Ni?Ni?Al?O?linkage, rather than by chemical bonding with Ni?O bonds from ?Ni?Ni?Ni?O?Al?O? or chemical reaction forming spinel interphases.